An LGBTQ+ mentorship program enriched the experience of medical students and physician mentors - Beanlands, Rachelle; Robinson, Lilian; Venance, Shannon (Canadian Medical Education Journal, 2020)
Implication Statement The Schulich School of Medicine and Dentistry LGBTQ+ mentorship program positively impacted the personal and professional experience of LGBTQ+ medical students and physician mentors. Mentorship delivered by LGBTQ+ physicians fostered a safe environment for self-expression, and provided mentees with experience-driven guidance in navigating the medical profession. We therefore recommend that all Canadian medical schools consider the longitudinal implementation of an LGBTQ+ mentorship program to support the personal and professional development of their LGBTQ+-identifying students.